Bionanofiber Assisted Decoration of Few‐Layered MoSe2 Nanosheets on 3D Conductive Networks for Efficient Hydrogen Evolution. Issue 7 (5th December 2016) - Lai, Feili; Yong, Dingyu; Ning, Xueliang; Pan, Bicai; Miao, Yue‐E; Liu, Tianxi
Abstract : Molybdenum diselenide (MoSe2 ) has emerged as a promising electrocatalyst for hydrogen evolution reaction (HER). However, its properties are still confined due to the limited active sites and poor conductivity. Thus, it remains a great challenge to synergistically achieve structural and electronic modulations for MoSe2 ‐based HER catalysts because of the contradictory relationship between these two characteristics. Herein, bacterial cellulose‐derived carbon nanofibers are used to assist the uniform growth of few‐layered MoSe2 nanosheets, which effectively increase the active sites of MoSe2 for hydrogen atom adsorption. Meanwhile, carbonized bacterial cellulose (CBC) nanofibers provide a 3D network for electrolyte penetration into the inner space and accelerate electron transfer as well, thus leading to the dramatically increased HER activity. In acidic media, the CBC/MoSe2 hybrid catalyst exhibits fast hydrogen evolution kinetics with onset overpotential of 91 mV and Tafel slope of 55 mV dec −1, which is much more outstanding than both bulk MoSe2 aggregates and CBC nanofibers. Furthermore, the fast HER kinetics are well supported by theoretical calculations of density‐functional‐theory analysis with a low activation barrier of 0.08 eV for H2 generation. Hence, this work highlights an efficient solution to develop high‐performance HER catalysts by incorporating biotemplate materials, to simultaneously achieve increased active sites and conductivity. Abstract : Bacterial cellulose‐derived carbon nanofibers are used to successfully assist the uniform growth of few‐layered MoSe2 nanosheets, which is beneficial to synergistically achieve structural and electronic modulations for MoSe2 ‐based hydrogen evolution reaction catalysts.